1999
DOI: 10.1002/(sici)1097-4652(199911)181:2<273::aid-jcp9>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cell growth and transformation by doxycycline‐regulated FGF‐2 expression in NIH‐3T3 cells

Abstract: The single-copy fibroblast growth factor 2 (FGF-2) gene encodes four coexpressed isoforms of different molecular masses. The 18-kDa FGF-2 is primarily localized in the cytoplasm, whereas the higher molecular mass isoforms (HMW FGF-2) localize to the nucleus and nucleolus. The overexpression of either 18-kDa FGF-2 or HMW FGF-2 promotes cell transformation in a dose-dependent manner. In NIH 3T3 cells, the selective overexpression of HMW FGF-2 but not of 18-kDa FGF-2 confers upon the cells the unique phenotype of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The isoforms exert different biological effects when overexpressed in different cell types. Specific effects seen by the 23-kDa isoform but not the 18-kDa isoform after overexpression are reduced spreading of pancreatic cancer cells (4), the ability of NIH 3T3 cells to grow in low serum medium (5), increased radioresistance in HeLa cells (6), growing in serumfree medium of rat AR4 -2J cells (7), and differential effects on binucleation and nuclear morphology of neonatal rat cardiac myocytes (8). We have previously shown that in PC12 cells and rat immortalized Schwann cells, cell growth and morphology are altered after transfection with constructs coding for 18-and 23-kDa FGF-2, respectively (9,10).…”
mentioning
confidence: 99%
“…The isoforms exert different biological effects when overexpressed in different cell types. Specific effects seen by the 23-kDa isoform but not the 18-kDa isoform after overexpression are reduced spreading of pancreatic cancer cells (4), the ability of NIH 3T3 cells to grow in low serum medium (5), increased radioresistance in HeLa cells (6), growing in serumfree medium of rat AR4 -2J cells (7), and differential effects on binucleation and nuclear morphology of neonatal rat cardiac myocytes (8). We have previously shown that in PC12 cells and rat immortalized Schwann cells, cell growth and morphology are altered after transfection with constructs coding for 18-and 23-kDa FGF-2, respectively (9,10).…”
mentioning
confidence: 99%
“…For instance, expression of the LMW FGF-2 enhances cell migration (10) and increases integrin (19), tissue plasminogen activator, and PKC⑀ expressions (20,21). By contrast, the HMW FGF-2 specifically promotes cell growth at low serum concentration (10,22,23), reduces cell migration (10,20), expression of laminin B1 (8), tissue plasminogen activator (20), plasminogen activator inhibitor-1 (20), PKC⑀ (21), adenylate cyclase activity (24), and inhibits interleukin-6 promoter activity (25). In these reports, which also include the cell line AR4-2J-A3 used in the present study, addition of neutralizing anti-FGF-2 antibodies, which recognize the common sequence of all FGF-2 forms, or expression of a dominant negative FGF receptor-1 were found to counteract the biological effects of the extracellular FGF-2 but not those of the HMW FGF-2 (10, 20, 26 -28).…”
mentioning
confidence: 99%
“…For instance, expression of the LMW form enhances cell migration (10), integrin, and tissue plasminogen activator expressions (15), whereas the HMW FGF-2 does not affect these properties. By contrast, the HMW form specifically promotes, at the difference of the LMW form, growth at low serum con-centration (0 -1%) (10,16,17), reduces laminin B1 (8), tissue plasminogen activator and plasminogen activator inhibitor-1 expression (18), adenylate cyclase activity (19), and inhibits interleukin-6 promoter activity (20). Furthermore, neutralizing anti-FGF-2 antibodies recognizing the common sequence of all FGF-2 forms (10,21), suramin (18), a well established inhibitor of FGF-2 binding to FGF receptors (22), and expression of high level of dominant negative FGFR (10) inhibit the biological effects of the extracellular FGF-2, but they do not modify those evoked by the HMW FGF-2.…”
mentioning
confidence: 99%